Noninvasive Imaging Test to Assess Liver Fibrosis: Vibration-controlled Transient Elastography - Mi Na Kim (The Korean Journal of Gastroenterology)
Liver fibrosis refers to the formation of scar tissue in the liver when inflammation persists over a long period. Assessing liver fibrosis is crucial for predicting the prognosis of chronic liver disease and managing patients with these conditions. Although a liver biopsy remains the gold standard for assessing liver fibrosis, it is limited by its invasive nature. Consequently, continuous efforts have been made to develop non-invasive methods for evaluating liver fibrosis, including imaging techniques and serum biomarkers. Vibration-controlled transient elastography (VCTE), a representative non-invasive imaging technique, has been used widely for liver fibrosis assessment since its introduction in 2003. This paper discusses the principles and methods of measurement, the advantages and disadvantages, and the considerations for interpreting VCTE based on the 2024 KASL Clinical Practice Guidelines for Non-invasive Tests to Assess Liver Fibrosis in Chronic Liver Disease. In addition, the diagnostic utility of VCTE in chronic viral hepatitis is reviewed.